A 12.3-kb Duplication Within the VWF Gene in Pigs Affected by Von Willebrand Disease Type 3. Issue 2 (1st February 2018) - Lehner, Stefanie; Ekhlasi-Hundrieser, Mahnaz; Detering, Carsten; Allerkamp, Hanna; Pfarrer, Christiane; von Depka Prondzinski, Mario
Abstract: Von Willebrand Disease (VWD) type 3 is a serious and sometimes fatal hereditary bleeding disorder. In pigs, the disease has been known for decades, and affected animals are used as models for the human disease. Due to the recessive mode of inheritance of VWD type 3, severe bleeding is typically seen in homozygous individuals. We sequenced the complete porcine VWF (Von Willebrand Factor) complementary DNA (cDNA) and detected a tandem duplication of exons 17 and 18, causing a frameshift and a premature termination codon (p.Val814LeufsTer3) in the affected pig. Subsequent next generation sequencing on genomic DNA proved the existence of a 12.3-kb tandem duplication associated with VWD. This duplication putatively originates from porcine Short Interspersed Nuclear Elements (SINEs) located within VWF introns 16 and 18 with high identity. The premature termination truncates the VWF open reading frame by a large part, resulting in an almost entire loss of the mature peptide. It is therefore supposed to account for the severe VWD type 3. Our results further indicate the presence of strong, nonsense-mediated decay in VWF messenger RNA (mRNA) containing the duplication, which was supported by the almost complete absence of the complete VWF protein in immunohistochemistry analysis of the VWD-affected pig. In the past, differentiation of wild-type and heterozygous pigs in this VWD colony had to rely on clinical examinations and additional laboratory methods. The present study provides the basis to distinguish both genotypes by performing a rapid and simple genetic analysis.